Use of a low-tech tool in the improvement of social interaction of patients with Rett Syndrome: an observational study - Caprì, Tindara; Dovigo, Lucia; Semino, Martina; Lotan, Meir; Mohammadhasani, Nasrin; Zamarra, Giuseppina; Fabio, Rosa Angela (Frontiers in Public Health, 2024)
The main aim of the present study was to examine whether the use of a low-tech tool, called click4all, inserted into cognitive and motor training can increase social interaction of patients with Rett Syndrome (RTT) with classmates in a school setting. Methods: Twenty-seven participants with RTT were randomly assigned to two groups: the experimental group received treatment with click4all, and the control group received traditional treatment without click4all. Parameters were measured before treatment (T1), six months after treatment (T2), six months after the second treatment phase (T3) and at the end of the third treatment phase (T4). Results: The results demonstrated an increase in levels of social interaction among classmates and patients with RTT in the experimental group, over time, compared to the control group, 95% ]. Classmates also showed a higher level of knowledge related to participants of the experimental group, and this increased over time, 95% ]. The level of knowledge related to the control group was stable over time and lower than the experimental group. Discussion: This study demonstrated that the use of a low-tech tool can increase social interactions of patients with RTT in a school setting. This is important, as patients with RTT are often restricted in an isolation condition.